2007
DOI: 10.1590/s0034-89102006005000041
|View full text |Cite
|
Sign up to set email alerts
|

Competência de peixes como predadores de larvas de Aedes aegypti, em condições de laboratório

Abstract: OBJECTIVE:To evaluate the effi cacy of fi sh as predators of the Aedes aegypti larvae in laboratory conditions. METHODS:The male and female of fi ve different fi sh were included in the experiment. The tests to measure their consumption ability lasted fi ve weeks for each species. Each trial involved four test tanks and four control tanks. Two control tanks contained just one fi sh, and the other two just larvae. Each of the test tanks contained one fi sh and the larvae. During the fi rst week, 100 larvae were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 10 publications
1
15
0
9
Order By: Relevance
“…Poecilia reticulata) (Peter, 1859) have been suggested in several countries and regions for mosquito control, mainly for Ae. aegypti (Hoy, 1985;Das and Prasad, 1991;Cavalcanti et al, 2007;Walton, 2007;Chandra et al, 2008;Seng et al, 2008;Dumont and Chiroleu, 2010;Kweka et al, 2011;Kamareddine, 2012;Shulse et al, 2013;Pereira and Oliveira, 2014;Chobu et al, 2015;. More natural mosquito predators, including copepods [e.g.…”
Section: Control and Prophylaxismentioning
confidence: 99%
“…Poecilia reticulata) (Peter, 1859) have been suggested in several countries and regions for mosquito control, mainly for Ae. aegypti (Hoy, 1985;Das and Prasad, 1991;Cavalcanti et al, 2007;Walton, 2007;Chandra et al, 2008;Seng et al, 2008;Dumont and Chiroleu, 2010;Kweka et al, 2011;Kamareddine, 2012;Shulse et al, 2013;Pereira and Oliveira, 2014;Chobu et al, 2015;. More natural mosquito predators, including copepods [e.g.…”
Section: Control and Prophylaxismentioning
confidence: 99%
“…Laboratory experiments have identified different fish species that feed on larvae [11, 12]. Authors in Gujarat, India, reported that the native Aphanius dispar (Ruppell) fish is capable of consuming three types of mosquito larvae, including Aedes aegypti [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators combatted against Aedes larvae utilizing poecilid larvivorous fish guppy and platy (Poecilia reticulata and Xiphophorus maculatus, respectively) in natural monitored habitats (Pamplona et al, 2004) as well as employing these fish in confined containers (Cavalcanti et al, 2007;Pereira and Oliveira, 2014).…”
mentioning
confidence: 99%
“…Despite the abundance of guppies and platys and information on their ability to effectively control mosquito larvae (Cavalcanti et al, 2007) and data on toxicological effects of insecticide exposure in aquatic environment that are available (Abe et al, 2014;Meng et al, 2013;Kaya et al, 2013;Shun et al, 2013), the simultaneous use of fish with larvicides in Brazil against mosquito survival has not been exploited. Thus, the aim of this study was to assess under a realistic exposure scenario to Aedes larvae whether concurrent use of larvivorous fish and a natural larvicide might provide more effective protection against the mosquito population.…”
mentioning
confidence: 99%